Placental pathology and neonatal morbidity: exploring the impact of gestational age at birth - Elisabeth B. Budal; Jørg Kessler; Geir Egil Eide; Cathrine Ebbing; Karin Collett (BMC, 2024)
Abstract Aim To evaluate placental pathology in term and post-term births, investigate differences in clinical characteristics, and assess the risk of adverse neonatal outcome. Methods This prospective observational study included 315 singleton births with gestational age (GA) > 36 weeks + 6 days meeting the local criteria for referral to placental histopathologic examination. We applied the Amsterdam criteria to classify the placentas. Births were categorized according to GA; early-term (37 weeks + 0 days to 38 weeks + 6 days), term (39 weeks + 0 days to 40 weeks + 6 days), late-term (41 weeks + 0 days to 41 weeks + 6 days), and post-term births (≥ 42 weeks + 0 days). The groups were compared regarding placental pathology findings and clinical characteristics. Adverse neonatal outcomes were defined as 5-minute Apgar score < 7, umbilical cord artery pH < 7.0, admission to the neonatal intensive care unit or intrauterine death. A composite adverse outcome included one or more adverse outcomes. The associations between placental pathology, adverse neonatal outcomes, maternal and pregnancy characteristics were evaluated by logistic regression analysis. Results Late-term and post-term births exhibited significantly higher rates of histologic chorioamnionitis (HCA), fetal inflammatory response, clinical chorioamnionitis (CCA) and transfer to neonatal intensive care unit (NICU) compared to early-term and term births. HCA and maternal smoking in pregnancy were associated with adverse outcomes in an adjusted analysis. Nulliparity, CCA, emergency section and increasing GA were all significantly associated with HCA. Conclusions HCA was more prevalent in late and post-term births and was the only factor, along with maternal smoking, that was associated with adverse neonatal outcomes. Since nulliparity, CCA and GA beyond term are associated with HCA, this should alert the clinician and elicit continuous intrapartum monitoring for timely intervention.